Serratia spp. as plant growth-promoting bacteria alleviating salinity, drought, and nutrient imbalance stresses - Kulkova, Iryna; Wróbel, Barbara; Dobrzyński, Jakub (Frontiers in Microbiology, 2024)
Plants in agricultural environments are often exposed to abiotic stresses, including temperature extremes, salt stress, drought and heavy metal soil contamination, leading to significant economic losses worldwide. Among these stresses, salt stress and drought pose serious challenges, inducing ionic toxicity, osmotic stress and oxidative stress in plants. This review highlights the potential of Serratia spp., a genus of gram-negative, facultatively anaerobic bacteria, as plant growth-promoting bacteria (PGPB) to mitigate these environmental challenges. Serratia spp. strains exhibit a variety of mechanisms, such as phytohormone production, ACC deaminase activity, nitrogen fixation, P and Zn solubilisation, antioxidant properties, and gene expression, contributing to enhanced plant growth and stress tolerance. Exploration of these mechanisms highlights the importance of further research to unlock the full potential of Serratia spp. as biofertilizers for sustainable agriculture, offering a valuable contribution to the development of environmentally friendly practices in the context of global agricultural challenges.